Hypoglykémie a těsná kontrola glykémie u kriticky nemocných pacientů - Vriesendorp, Titia M; DeVries, J. Hans; Hoekstra, Joost B. L (Current Opinion in Critical Care (České vyd.), 2008)
In contrast to patients with diabetes mellitus, data on consequences of hypoglycemia in critically ill patients are sparse. The purpose of this review is to summarize available data on prevalence of hypoglycemia, risk factors, and possible consequences of hypoglycemia in critically ill patients. RECENT FINDINGS: There is strong evidence that strict glycemic control is beneficial for critically ill patients. Recent attempts to confirm these findings have not succeeded. Instead, they have increased the fear for negative consequences of hypoglycemia. Hypoglycemia is four to seven times more frequent in patients treated with strict glycemic control. Risk factors for hypoglycemia are a change in nutrition without adjustment of insulin treatment, diabetes mellitus, sepsis, shock, liver failure, and the need for renal replacement therapy. Consequences of hypoglycemia in critically ill patients are not well defined, but overall current evidence suggests that beneficial effects of strict glycemic control outweigh possible negative effects of hypoglycemia. SUMMARY: Hypoglycemia should be avoided in critically ill patients, but not at the cost of less stringent glycemic control. Strict glycemic control with a low incidence of hypoglycemia can be achieved with a validated (computerized) algorithm and increased surveillance in patients with an increased risk for hypoglycemia.
Keywords: hypoglykemie; kritický stav; Hypoglycemia; Intensive Care Units; Humans; lidé; jednotky intenzivní péče; Blood Glucose; krevní glukóza; Glycemic Index; glykemický index; Critical Illness